Assistance in Public Financial Management and Thematic Village Exploration and Review of Management Potential Economical Value of Organic Waste: Pendampingan Pengelolaan Keuangan Publik dan Eksplorasi Desa Tematik serta Peninjauan Potensi Pengelolaan Sampah Organik Bernilai Ekonomis - Suwarno; Bambang Pamungkas; Aang Munawar; Mumuh Mulyan; Ani Mekaniwati; Budi Setiawan; Tarida Marlin Surya Manurung; Sutarti; Sudradjat; Annaria Magdalena M.; Dwi Maulina; Indra Bayu Permana (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Villages are the main focus of state development, with managing village funds becoming a crucial issue. Law Number 6 of 2014 concerning Villages sets the state's goal to protect and empower villages to become firm, advanced, independent, and democratic. An Independent Village is a developed village that can lead development by paying attention to economic and ecological resilience. Good village financial management and village independence are crucial to improving the community's economy. Villages' main challenges involve managing complex data, limited resources, and changing organizational culture. The use of technology, efficient public financial management systems, training, and participation of civil society organizations are proposed as solutions to overcome these challenges. The Kesatuan Business and Informatics Institute is collaborating with the local government of Tanah Bumbu, South Kalimantan, to increase insight regarding public financial management and develop village potential. The IBIK PkM team provides solutions in the form of (1) assistance regarding accountable public financial management, and (2) socialization of the Systematic & Integrated Village (DE Siti) application. Partners were invited to conduct a field visit to The Thematic Perca Village and organic waste management (Siliwangi Waste Bank Unit).